2010
DOI: 10.1016/j.icarus.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity experiments on the collisional behavior of saturnian ring particles

Abstract: In this paper we present results of two novel experimental methods to investigate the collisional behavior of individual macroscopic icy bodies. The experiments reported here were conducted in the microgravity environments of parabolic flights and the Bremen drop tower facility. Using a cryogenic parabolic-flight setup, we were able to capture 41 near-central collisions of 1.5-cm-sized ice spheres at relative velocities between 6 and . The analysis of the image sequences provides a uniform distribution of coef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 46 publications
10
68
5
Order By: Relevance
“…This demonstrates that the limit of coefficient of restitution decreases with increasing impact velocity, which is corroborated by Güttler et al (2012) and Krijt et al (2013). It is also possible that this is a result of deviation from sphericity (compared to the results of Heißelmann et al (2010) who used almost perfectly spherical samples) or due to the smaller size of our particles.…”
Section: Coefficient Of Restitution and Impact Parametersupporting
confidence: 86%
See 2 more Smart Citations
“…This demonstrates that the limit of coefficient of restitution decreases with increasing impact velocity, which is corroborated by Güttler et al (2012) and Krijt et al (2013). It is also possible that this is a result of deviation from sphericity (compared to the results of Heißelmann et al (2010) who used almost perfectly spherical samples) or due to the smaller size of our particles.…”
Section: Coefficient Of Restitution and Impact Parametersupporting
confidence: 86%
“…7a, the coefficients of restitution have an upper limit of 0.65. Similar experiments by Heißelmann et al (2010) on collisions of 1.5 cm (diameter) ice spheres in the velocity range 0.06-0.22 m s −1 gave an upper limit of 0.84 (also shown in Fig. 7a).…”
Section: Coefficient Of Restitution and Impact Parametersupporting
confidence: 74%
See 1 more Smart Citation
“…More recent experiments showed that collisions of mm-to cm-sized aggregates often result in bouncing (e.g., Weidling et al 2009;Heißelmann et al 2010;Weidling et al 2012;Jankowski et al 2012). Extrapolating the results obtained from the various experiments, Güttler et al (2010) devised a model describing the outcome of collision with respect to the collision velocity, and the mass and porosity of the colliding aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modeling, including all different kinds of collisions then result in a boucing barrier ). However, the most pronounced input is that only rebound was observed in collisions of mm-size aggregates in the relevant domain of low collision velocities (Heißelmann et al 2010;Weidling et al 2012). The experiments that are important used dust with grain sizes of about 1 μm.…”
Section: Resultsmentioning
confidence: 99%